Stress Alarm Raiser Based on Facial Expressions (International Journal of Innovative Research in Computer Science & Technology, 2023)
This paper presents the development of a  stress detector using facial expression analysis in Python,  utilizing the Deep Face library. Also, after detecting  whether the person is in stress or not, it allows the user to  inform about his stress to the preferred his/her family  member by sending an automated WhatsApp message and  showing some remedies to reduce stress.
Keywords: Emotion Detection; Deep Face; Facial Expression Detection